Transformational Leadership Model Of School Principals In Empowerment Teachers As Multicultural Capital (A Holistic Single Case Study at SMA SPI Batu City, Indonesia) - Aan Fardani Ubaidillah (Universitas Islam Raden Rahmat Malang, 2022)
Abstract: This research focuses on the transformational leadership model of school principals in empowering teachers as multicultural capital at SMA SPI Batu City, Indonesia. The study aims to understand and finding the role of school principals in promoting multiculturalism and developing multicultural capital in the educational environment. A qualitative approach was employed, using a holistic single case study at SMA SPI, with data collected through participant observation, in-depth interviews, and document analysis. The findings demonstrate the interrelationships between the dimensions of teachers' multicultural capital, the feedback provided by the principal's transformational leadership, and the objectives of the feedback on the teacher's multicultural dimension. The principal's feedback aims to foster multicultural understanding, enhance inclusive teaching practices, promote effective intercultural communication, and organize multicultural activities. The study emphasizes the crucial role of the principal's transformational leadership in empowering teachers and creating an inclusive and culturally responsive learning environment. The findings contribute valuable insights into how principal leadership can build multicultural capital in educational institutions, promoting respect, inclusivity, and academic growth among students. Keywords: Leadership Model, Transformational Leadership, Multicultural Capital, School Principal.